منهج ابن عادل الحنبلي في إيراد القراءات الأربع عشرة وأثرها في تفسيره الفاتحة والبقرة نموذجا - Sajjad Faisal Taha Alhumaidan (Universiti Sains Islam Malaysia, 2018)
Thesis (M.A)--Faculty of Quranic and Sunnah Studies, Universiti Sains Islam Malaysia, 2015